Recent Study on Dermatoglyphic Ulnar Loops in Turner’s Syndrome - Yadav, Aruna Y.; Satpute, Supriya P.; More, Swati (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
The purpose of this research was to compare the ulnar loops of dermatoglyphics in Turner's syndrome females and control females. The present study used bilateral rolled finger prints and palm prints from 40 Turner's syndrome patients. They were between the ages of 14 and 20. Clinical examination and chromosomal analysis were used to make the diagnosis, and patients with the 45 XO karyotype were chosen. Normal healthy females between the ages of 14 and 20 were chosen as controls. Ulnar loops became more common in the I3 and I4 areas. It is extremely important in this area.